2014
DOI: 10.1111/acps.12258
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive symptoms in at‐risk mental states for psychosis: associations with clinical impairment and cognitive function

Abstract: Findings extend upon previous results due to the multidimensional assessment. Subsequent longitudinal studies might elucidate how comorbid OCS influence differential treatment response, especially to cognitive behavioural interventions and the transition rates to psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 71 publications
3
29
0
Order By: Relevance
“…In fact, a categorical approach might not be appropriate to capture such dual relationship of PS impairment along a severity continuum of OC dimension. The finding of a direct association between severe OCS and PS scores (the "obsessive paradox") is in line with previous studies, which suggested a positive effect of comorbid OCS on specific cognitive functions (especially executive functions and working memory) either in patients with schizophrenia (Borkowska et al, 2003;Kontis et al, 2016;Lee et al, 2009) or in individuals with at-risk mental states for psychosis (Soyata et al, 2018;Zink et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a categorical approach might not be appropriate to capture such dual relationship of PS impairment along a severity continuum of OC dimension. The finding of a direct association between severe OCS and PS scores (the "obsessive paradox") is in line with previous studies, which suggested a positive effect of comorbid OCS on specific cognitive functions (especially executive functions and working memory) either in patients with schizophrenia (Borkowska et al, 2003;Kontis et al, 2016;Lee et al, 2009) or in individuals with at-risk mental states for psychosis (Soyata et al, 2018;Zink et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…While some studies found OCS to be linked to cognitive deficits , others found no evidence for cognitive differences between schizophrenia patients with or without co‐occurring OCS . Some studies even reported better performance of the comorbid group within patients with schizophrenia or in the at risk mental state of psychosis .The inconsistency of results may partly be explained by the cross‐sectional nature of most studies. To the best of our knowledge, only two studies prospectively assessed neurocognitive functioning in comorbid samples over time.…”
Section: Introductionmentioning
confidence: 96%
“…A recent study found that 13% of at-risk mental state patients reported OCS, while 5.4% fulfilled the criteria for OCD. Slightly higher averaged rates for OCS (17.1%) and OCD (7%) were found in first-episode patients (Zink et al, 2014). These rates are significantly lower than that descripted in cross sectional studies of chronic or late stage, as described above.…”
Section: Introductionmentioning
confidence: 61%
“…The presence of OCS in schizophrenia seems to be associated with poor outcomes such as earlier age of onset (Faragian et al, 2012), poorer treatment response (Zink et al, 2014), more depressive (de Haan et al, 2013) and negative symptoms (Owashi et al, 2010) and greater cognitive deficits (Patel et al, 2010;Schirmbeck et al, 2013b). It remains unknown whether treatment for the OCS reverts these outcomes.…”
Section: Introductionmentioning
confidence: 99%